Living longer, living better exploring the heart-mind connection - Opie, Lionel H. (Oxford : Oxford University Press, 2011)
Aimed at those who strive for optimal long-term health and the maximal functioning of their hearts and minds,'Living Longer' sifts through the often conflicting information available on the vast number of possible health promotion changes. It isolates five key steps to promote long-term health benefits for the heart and mind.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Longevity; Heart -- Aging; Brain -- Aging; Heart -- Diseases -- Prevention; Brain -- Degeneration -- Prevention; Self-care, Health